MODEL HUMAN CAPITAL PETUGAS PENYULUH LAPANGAN TERHADAP SERVQUAL PADA MASA PANDEMI CORONA DI BADAN PENYULUHAN PERTANIAN DAN KEHUTANAN KECAMATAN MENYUKE KABUPATEN LANDAK - Kurniawan, Hery Medianto; Aini, Fitriana (Jurnal Ekonomi STIEP, 2021)
This study aims to create a human capital modeling for field extension officers during the corona pandemic at the Agricultural and Forestry Extension Agency, Menyuke District, Landak Regency. This modeling is intended for how the PPL human capital at BP2K Menyuke should provide outreach services during the corona pandemic. This modeling is very important because the corona pandemic does not allow outreach activities to be carried out as in normal conditions. However, even though the corona pandemic still occurs, service activities by PPLs must continue to run well, so that the achievement of objectives in extension activities can be achieved and the desire of farmers to get good service and according to expectations can also be achieved. The target of this research is to produce a PPL human capital model against service quality at BP2K Menyuke. This modeling will be seen based on service and quality dimensions which include tangible, reliability, responsiveness, assurance, and empathy. Modeling approach through Gap Analysis. The human capital model for service quality during the corona pandemic at BP2K Menyuke is the IT-based smartPP (source, message, attitude, receiver, taste) model. The source or sender of the message is the source of the message. Message or messages in the SmartPP Model are the substances sent by the source or source to the recipient of the message. Attitudes (attitudes) are attitudes given by the recipient of the message before and after receiving the message. Receiver or message receiver refers to the individual who receives the message sent by the sender of the message. Taste (feel), in doing the result of communication, thirst is usually felt